Multidimensional social and cultural norms influencing HPV vaccine hesitancy in Asia - Li Ping Wong; Pooi-Fong Wong; Megat Mohamad Amirul Amzar Megat Hashim; Liyuan Han; Yulan Lin; Zhijian Hu; Qinjian Zhao; Gregory D. Zimet (Taylor & Francis Group, 2020)
HPV vaccine hesitancy in Asia is unique compared to Western countries due to multidimensional social-cultural norms that influence beliefs regarding vaccination. Reviews on HPV vaccine hesitancy in Asia lack of in-depth discussion regarding the traditional and social-cultural norms dimensions. This paper puts forward opinions in which culture, normative beliefs, and religion influence HPV vaccine hesitancy in Asian countries. Issues surrounding HPV hesitancy among parents, young adult women, adult women, men and the sexual and gender minority people in Asian countries were highlighted. The shortage of HPV vaccine supply would soon be reduced as some Asian countries are on the way to producing the HPV vaccine which production is currently dominated by Western European countries. The culture of favoring imported Western products among many in Asia and in addition to long-existing fake vaccine crisis pose a challenge for the newly emerging HPV vaccine produced in Asia. Some recommendations, research gaps, and future research needs were discussed.